Pursuing Entrepreneurial University: Breakdown The Self-Assessment Model - Novela, Selly; Syarief, Rizal; Fahmi, Idqan; Arkeman, Yandra (International Review of Management and Marketing, 2020)
In this era of turbulence, the entrepreneurial university model is considered the most appropriate concept in responding to the challenges and demands of higher education in the future. Entrepreneurial universities emerged as a response to the interests of knowledge within the scope of innovation systems, both nationally and regionally. Transformation into an entrepreneurial university becomes a search for universities that want to ensure their sustainability. The purpose of this study is to help university in conducting self-assessment to get a clear understanding of the situation at hand. Pursuing an entrepreneurial university requires a long process and sufficient capabilities. From the breakdown of existing models, it is known that it is not enough for universities to achieve output only, but must lead to clearer outcomes so that the role in economic growth becomes more apparent. Keywords: Breakdown, Entrepreneurial University, Self-Assessment, Transformation JEL Classifications: I25, O15 DOI: https://doi.org/10.32479/irmm.10356